The Cambridge introduction to J.M. Coetzee - Head, Dominic (Cambridge introductions to literature., 2009)
The South African novelist and Nobel Laureate J.M. Coetzee is widely studied around the world and attracts considerable critical attention. with the publication of Disgrace Coetzee began to enjoy popular as well as critical acclaim, but his work can be as challenging as it is impressive. This book is addressed to students and readers of Coetzee: it is an up-to-date survey of the writer's fiction and context, written accessibly for those new to his work. All of the fiction is discussed, and the brooding presence of the political situation in South Africa, during the first part of his career, is given serious attention in a comprehensive account of the author's main influences. The revealing strand of confessional writing in the latter half of Coetzee's career is given full consideration. This Introduction will help new readers understand and appreciate one of the most important and challenging authors in contemporary literature.